2020
DOI: 10.21203/rs.3.rs-79029/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Brain-Behavior Space Relationships Along the Psychosis Spectrum

Abstract: Difficulties in advancing effective patient-specific therapies for psychiatric disorders highlights a need to develop a neurobiologically-grounded, quantitatively stable mapping between neural and symptom variation. This gap is particularly acute for psychosis-spectrum disorders (PSD). Here, in a sample of 436 cross-diagnostic PSD patients, we derived and replicated a data-driven dimensionality-reduced symptom space across hallmark psychopathology symptoms and cognitive deficits, which was predictive at the si… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…1I; r=-0.46 p=0.033 permutation test, n=20 mice). These results are consistent with the spectrum of behavior and functional connectivity seen in humans [2][3][4][5] , highlighting the face validity of the VPA model.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…1I; r=-0.46 p=0.033 permutation test, n=20 mice). These results are consistent with the spectrum of behavior and functional connectivity seen in humans [2][3][4][5] , highlighting the face validity of the VPA model.…”
supporting
confidence: 84%
“…Understanding how individual differences in behavior relate to differences in neural activity is critical for developing individualized treatments of neuropsychiatric and neurodevelopmental disorders. Considerable work has linked behavioral variability to differences in how correlated neural activity is between brain areas, termed ‘functional connectivity.’ For example, patterns in functional connectivity vary across individuals 2 and are disrupted in autism 3 , schizophrenia 4 , and depression 5 . However, the changes in neural activity that underlie this altered functional connectivity remain unclear.…”
Section: Mainmentioning
confidence: 99%
“…This new symptom structure could aid in elucidating the underlying biopsychosocial causes of symptoms, informing and improving clinical practice. In fact, recent neuroimaging research has shown that PCA components were superior for identifying robust correlates of brain connectivity compared to traditional scale sub-scores 33 . Our framework could also inform computational understanding of reality monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the relationship between these genes and human behaviors, we leveraged the stable brain-behavior space strategy proposed by Ji et al [27], which could be briefly divided into the following three sections. These procedures were called Behavioral-FC-Gene mapping analysis to facilitate a better understanding and fluency of the paper.…”
Section: Methodsmentioning
confidence: 99%
“…One promising approach is imaging-transcriptomics analysis [2426], which allows the brain-wide spatial analysis of microscopic transcriptome data combined with macroscopic neuroimaging phenotypes [9]. Moreover, it also offers the opportunity to link the transcriptome data with the behavior variations via the neuroimaging [27]. These cross-scale analyses could provide a better understanding of the interaction between microscale gene expression and macroscale functional network, and ultimately involved in the individual behaviors, and importantly, their putative multiscale interactions in cerebellar related diseases [28].…”
Section: Introductionmentioning
confidence: 99%